PENGGUNAKAN SISTEM DINAMIK DALAM MANAJEMEN TRANSPORTASI UNTUK MENGATASI KEMACETAN DI DAERAH PERKOTAAN - Wiyono, Sugeng (Jurnal Transportasi, 2012)
Traffic congestion is part of the transportation problems which are always resolved using indicators and transportation modeling without considering the spatial or land use development sectors. Land use affects the development and attract the use of urban road network and, thereby, increases the traffic volume. Besides the traffic circulation will create traffic conflicts, congestion, delay, and reduce the traffic speed. Transportation problems can be anticipated by implementing an integrated transportation management system, using a computer program that is able to detect the problem as early as possible. Dynamic modeling can be used to model complex problems of urban transportation. The results of this study indicate that the dynamic systemmodeling can be used as a tool to estimate the space requirement, with modeling variables must be first determined, making it clear what to be assessed and how the data to be structured.Keywords: traffic congestion, transportation management, dynamic modelling